Regulating the disclosure of chemical additives in the hydraulic fracturing process: a comparative analysis between Canadian and South African Law - Mc Michael, Luke (Institute of Marine and Environmental Law, 2016)
Broadly defined, hydraulic fracturing is a stimulation technique used in the oil and gas industry to create additional permeability through creating fractures in an unconventional gas reservoir. Desktop estimates predict that shale deposits beneath the semi-desert Karoo region in South Africa could hold a reserve of up to 450 trillion cubic feet. After initially imposing a moratorium on fracturing throughout South Africa, the South African government has recently changed track and is now intent on pursuing hydraulic fracturing and shale gas extraction in the Karoo. Arguably one of the main concerns with regards to hydraulic fracturing in the water scarce Karoo is that the fluids used to fracture rock formations can contain chemical additives that could contaminate scarce water resources and pose a risk to human health. In order to be in a better position to protect the environment and their health, members of the public need access to information on what chemical additives are used in fracturing operations. South Africa's access to information regime is primarily regulated in terms of the Promotion of Access to Information Act, 2000 which gives effect to the right to access to information in section 32 of the Constitution of the Republic of South Africa. There is no guarantee that information on chemical additives will be disclosed or withheld as the Act allows companies to withhold information for a number of reasons, including that the information may constitute a trade secret or confidential commercial or technical information. In June 2015 South Africa adopted the Final Regulations for petroleum exploration and exploitation in terms of the Mineral and Petroleum Resources Development Act, 2002. The Final Regulations include specific provisions on disclosure on chemical additives. However, the Final Regulations are riddled with uncertainty and loopholes that may seriously impede their ability to protect water resources from the chemical additives contained in fracturing fluids. As currently framed it is unclear whether or not information on chemical additives must be publically disclosed. Some lessons can be learned from regulatory experience in Canada in Alberta and British Columbia, for example the public disclosure of chemical additives on the website www.fracfocus.ca. However, a number of loopholes have undermined the effectiveness of regulation in Canada. The most prominent loophole is the fact that companies frequently withhold information on the chemicals they use on the basis that this information is a trade secret. The dissertation concludes that it cannot be said that South Africa's laws that regulate the disclosure of chemical additives will guarantee that fracturing will occur in a manner that is constituent with the right to an environment that is not detrimental to a person's health and wellbeing.